Magnetofabrics of eclogites and ultramafic rocks from the Chinese Continental Scientific Drilling (CCSD) project: evidence for ultrahigh-pressure (UHP) texture inheritance throughout retrogression - Grimmer, J. C.; Qi, X.; Xu, Z. (TRABAJOS DE GEOLOGÍA, 2009)
Ultrahigh-pressure (UHP) mafic and ultramafic rocks from the Chinese Continental Scientific Drilling (CCSD) in the Maobei eclogite body of the Sulu ultrahigh-pressure metamorphic belt in eastern China were studied for their magnetofabrics in order to constrain fluid rock interactions and related ductile deformation. Our magnetofabric data imply that the magnetic fabric of the mafic and ultramafic rocks mimics the UHP fabric and survived retrogression. Accordingly, the amphibolite to greenschist grade fabric is inherited from the UHP stage, and retrogression should not have been associated with substantial ductile deformation in these lithologies.